CORROSION PROTECTION OF STAINLESS STEEL TYPE 304 USING GRAPHENE COMPOSITES - Alhumade, Hesham; Nauman, Hiba; Elkamel, Erij; Yu, Aiping; Elkamel, Ali (MATTER: International Journal of Science and Technology, 2015)
Polyetherimide-Graphene (PEI/G) composites were prepared using in situ polymerization approach and thermally cured under vacuum on Stainless Steel 304 (SS304) substrates in order to be evaluated as corrosion protection coatings. Several steps curing were performed to ensure complete imidization of PEI/G composites. Dispersion of the graphene fillers in the PEI matrices was captured using Scanning electron microscopy (SEM) and Transmission electron microscopy (TEM). The study examines PEI/G composites as corrosion protection coatings using electrochemical techniques such as Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS). Furthermore, the influences of the load of graphene on the electrochemical behavior as well as the interface adhesion of the PEI/G composites are illustrated. Adhesion tests were conducted and evaluated according to ASTM D3359 standard and the long term performances of the prepared PEI/G coatings were confirmed by conducting the adhesion tests after 30 days of exposure to the corrosive medium. The study revealed that PEI may slow down the corrosion process on SS304 substrates and this protection property of PEI can be excelled by the incorporation of graphene in the PEI matrix.